Le Safari Historico-Gastronomique en Poitou-Charentes de Glen Baxter - Baxter, Glen (Petits Propos Culinaires, 2004)
This series of drawings was made for the journal L’Actualité Poitou-Charentes by the artist Glen Baxter. It is here reproduced in black and white with the artist’s permission. The cover to this issue shows one of the frames, not repeated on these pages, in its original colours. The identity of some of the regional specialities may be mysterious to the outsider. Broyé du Poitou is also called la fouée and is a round of bread dough topped with butter and cream. Le tourteau fromagé is made with fresh goat’s cheese (and latterly with cow’s milk). Larousse describes it as a gâteau shaped like a slightly flattened ball with a smooth, almost black surface. A deep pastry shell is filled with goat’s cheese, eggs, crème fraîche, sugar and flour. A cartelin is a regional version of a craquelin or cracker, a dry petit four, golden from a dusting of sugar, usually round with a scalloped border. It is linked to the échaudé (which was boiled before its baking) and the pretzel and was originally a Lenten delicacy. The petatou is a tart filled with potato purée and goat’s cheese, crème fraîche, sugar and eggs.